Sajiyä islam bilimliri tori (2016)
Webseite der Exil-Uiguren in der Türkei über den Islam. Diese Webseite hat zum Ziel, Grundzüge der islamischen Glaubenslehre, der Gesetzgebung und der islamischen Ethik zu vermitteln. - Website of the exiled Uyghurs in Turkey about Islam. The aim of this website is to convey basic principles of Islamic doctrine, legislation and Islamic ethics.